Design framework of the physical learning environment for children with autism / Roslinda Ghazali - Ghazali, Roslinda (2022)
They are unique and have a combination of characteristics; therefore, a designated learning environment should consider the sensory issues to overcome their needs. Several studies have shown that the quality learning environment has become significant, which affects learning outcomes. Previous studies by many researchers did not concerning the autistic environment. Issues were highlighted and only focused on sensory sensitivity, sensory stimulation, sensory design towards the physical learning environment. However, none of them is looking at the research concurrently and developing a framework. Therefore, this research will explore and develop a framework for sensory sensitivity, stimulation, and sensory design towards the physical learning environment to fill the study gap. This research investigation employed a quantitative approach by using a survey method to identify the factor of sensory sensitivity, sensory stimulation, sensory design, and physical learning environment. In addition, this study will also determine the respondents' awareness of knowledge and explore the relationship among those four variables.